Poverty as a Catalyst for Cybercrime: Evidence from Agona Swedru, Ghana - Paul Kwasi Kumah; Hubert Bimpeh Asiedu; Charles Obeng; Felix Awuah Obeng Senior (E-Journal of Humanities, Arts and Social Sciences)
Despite numerous efforts by stakeholders and institutions to mitigate social inequality and cybercrime globally, “these issues persist, particularly in developing countries like Ghana, where cybercrime has become a primary pursuit for many young people. This study aimed to examine the effect of social inequality on cybercrime and the mediating role of financial constraints. Using a quantitative research survey and a simple random sampling technique, 397 individuals were surveyed. The study’s findings revealed a positive and significant relationship between social inequality and cybercrime. There was also a significant positive relationship between social inequality and financial constraints. Additionally, a significant positive relationship was identified between financial constraints and cybercrime. The study also found a significant indirect effect of social inequality on cybercrime through financial constraints, indicating that financial constraints partially mediate the relationship between social inequality and cybercrime. Therefore, this study concluded that social inequality and financial constraints contribute significantly to the incidence of cybercrime in Agona Swedru and similar contexts. It is recommended that policymakers emphasize initiatives that promote equitable access to education, employment opportunities, and financial resources that alleviate the financial strain that pushes individuals toward cybercrime. By highlighting the link between social inequality and cybercrime while also revealing the mediating role of financial constraint, this study provides a comprehensive understanding of socioeconomic factors driving cybercrime.”